2016
DOI: 10.1007/s00436-016-4925-5
|View full text |Cite
|
Sign up to set email alerts
|

Description and molecular characterization of a new Leucocytozoon parasite (Haemosporida: Leucocytozoidae), Leucocytozoon californicus sp. nov., found in American kestrels (Falco sparverius sparverius)

Abstract: Diurnal raptors in the order Accipitriformes are commonly parasitized with Leucocytozoon spp., and the prevalence and intensity of parasitemia are often high. However, for raptors in Falconiformes, several studies have reported relatively low prevalences (1 % or less) of Leucocytozoon spp. Leucocytozoon parasite pathogenicity has been documented in falcons, but little is known about the diversity, prevalence, and phylogenetic relationships among Leucocytozoon species in these predatory birds. The research repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Leucocytozoon gametocytes, whose size was comparable to that described in kestrel by Sacchi and Prigioni [14]. However, parasite width and area agreed with the description reported by Walther et al [15].…”
Section: Discussionsupporting
confidence: 88%
“…Leucocytozoon gametocytes, whose size was comparable to that described in kestrel by Sacchi and Prigioni [14]. However, parasite width and area agreed with the description reported by Walther et al [15].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the haemosporidian lineages found in the sampled yellow‐rumped warblers are relatively generalist and have been found in other species in the MalAvi database (Bensch et al., ). For example, hDENPEN02 has been found in at least seven other species of Passeriformes in North America and lCNEORN01 in ten (Oakgrove et al., ; Outlaw & Ricklefs, ; Ricklefs & Fallon, ; Walther et al., ). Given these results, we suggest that it is unlikely that these parasites specialize and thereby exert differential levels of selection between myrtle and Audubon's warblers.…”
Section: Discussionmentioning
confidence: 99%
“…The group of seven Leucocytozoon lineages were identified in a distinct phylogenetic tree (S1 Fig) using Plasmodium juxtanucleare as the outgroup. Seven Leucocytozoon lineages joined in a clade with Leucocytozoon californicus described in the American kestrel ( Falco sparverius sparverius ) using molecular and microscopic approaches [50]. Among the 82 lineages described, the BULIBH1, BULIBP5, BULIBP13, BULIBP15, BULIBP42, and BULIBL77 lineages are classified as generalists, since they have been found in other avian genera and families (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…The Leucocytozoon phylogenetic tree showed that cattle egret lineages (BULIBL76 to BULIBL82) joined with the L . californicus lineage in a cluster that is more closely related to leucocytozoid lineages found in owls (families Tytonidae and Strigidae) and passerines (families Fringillidae and Emberizidae) [50].…”
Section: Discussionmentioning
confidence: 99%